Cultural transaction and early India: tradition and patronage - Thapar, Romila (Delhi, 1987)
A variety of beliefs about India's past have simmered over the last couple of hundred years. Some among them have come to be accepted. as part of the country's cultural tradition and have been accorded the status of tradition. It may be argued that this happens when societies are searching for identity and the pronouncements of historians, particularly of cultural historians, come to be accepted as axioms. It becomes necessary therefore for historians to pause from time to time to take stock as it were by asking whether what has come to be accepted as tradition deserves to be so accepted. This is what I propose to attempt in the two lectures. The change of focus becomes imperative either when there is new information on the past or when the process of interpreting the past undergoes change. It is primarily the latter which in this case suggests a re-assessment.
Keywords: India-culture